2004
DOI: 10.1128/jcm.42.3.1012-1015.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR with the Routine Procedure for Diagnosis of Tuberculosis in a Population with High Prevalences of Tuberculosis and Human Immunodeficiency Virus

Abstract: Direct smear examination with Ziehl-Neelsen (ZN) staining for the diagnosis of tuberculosis (TB) as employed in most low-income countries is cheap and easy to use, but its low sensitivity is a major drawback. The low specificity of chest X-rays, used for the diagnosis of smear-negative TB, risks high levels of overdiagnosis. Major advances in molecular techniques, which rapidly identify mycobacterial DNA in sputa, may overcome these obstacles. In this study, the AMPLICOR PCR system was used to diagnose pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 5 publications
7
63
0
4
Order By: Relevance
“…El cultivo del esputo posibilita el diagnóstico de cerca del 90% de los casos (16)(17)(18)(19)(20). En los pacientes que no expectoran, el lavado broncoalveolar, el aspirado gástrico y la biopsia pulmonar son procedimientos que se deben utilizar para la obtención de las muestras (19,20).…”
Section: Tuberculosis Establecidaunclassified
“…El cultivo del esputo posibilita el diagnóstico de cerca del 90% de los casos (16)(17)(18)(19)(20). En los pacientes que no expectoran, el lavado broncoalveolar, el aspirado gástrico y la biopsia pulmonar son procedimientos que se deben utilizar para la obtención de las muestras (19,20).…”
Section: Tuberculosis Establecidaunclassified
“…A previous study in Kenya showed that the sensitivity and specificity of this technique were 93% and 94%, respectively and did not affected by the HIV status (Kivihya-Ndugga et al, 2004, as cited in Cheepsattayakorn & Cheepsattayakorn, 2006.…”
Section: Amplicor Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Molecular (polymerase chain reaction [PCR]-or gene probe-based) tests generally perform less well on lower bacillary load smear-negative samples (107), suggesting lower sensitivity with HIV. However, one study showed high sensitivity for detecting TB in smearpositive sputum from HIV-infected subjects, using the AMPLI-COR PCR (Roche Diagnostic Systems, Branchburg, NJ) (99.7%), and no significant difference in sensitivity compared with smear-negative culture-positive specimens from HIV-negative subjects (89 vs. 95%) (108). Urine detection of the MTb cell wall component lipoarabinomannan may improve detection in smear-negative HIV-infected patients with advanced immunosuppression in a high-prevalence setting (109,110).…”
Section: Active Tb Disease Diagnosis In Hivmentioning
confidence: 99%